2023
DOI: 10.1111/imb.12835
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock regulates developmental time through ecdysone and juvenile hormones in Bombyx mori

Abstract: The circadian clock plays an integral role in hormone biosynthesis and secretion. However, how the circadian clock precisely coordinates hormonal homeostasis to maintain normal animal development remains unclear. Here, we show that knocking out the core clock gene Cryptochrome 1 (Cry1) significantly delays the developmental time in Bombyx mori. This study focuses on the ecdysone and juvenile hormone signalling pathways of fifth instar larvae with the longest developmental time delay. We found that the mutant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
3
5
0
Order By: Relevance
“…We observed expression of Zs‐adh, Zs‐dhr, Zs‐grh, Zs‐ghi, Zs‐hr4, Zs‐jhm, Zs‐jheh1, Zs‐jeh2, Zs‐jhe, Zs‐oshr , and Zs‐nhr3 in Z. scutellata . Consistent with our results, previous studies showed their different level of expression during several developmental stages in Spodoptera litura, B. dorsalis , and Bombyx mori (Qiu et al, 2023; Yang et al, 2016; Zhang et al, 2005). Juvenile hormone epoxide hydrolase ( jheh ) is an enzyme responsible for juvenile hormone metabolism is found in Z. scutellata ( Zs‐jheh1 and Zs‐jheh2 ) with relatively higher in current transcriptome study.…”
Section: Discussionsupporting
confidence: 93%
“…We observed expression of Zs‐adh, Zs‐dhr, Zs‐grh, Zs‐ghi, Zs‐hr4, Zs‐jhm, Zs‐jheh1, Zs‐jeh2, Zs‐jhe, Zs‐oshr , and Zs‐nhr3 in Z. scutellata . Consistent with our results, previous studies showed their different level of expression during several developmental stages in Spodoptera litura, B. dorsalis , and Bombyx mori (Qiu et al, 2023; Yang et al, 2016; Zhang et al, 2005). Juvenile hormone epoxide hydrolase ( jheh ) is an enzyme responsible for juvenile hormone metabolism is found in Z. scutellata ( Zs‐jheh1 and Zs‐jheh2 ) with relatively higher in current transcriptome study.…”
Section: Discussionsupporting
confidence: 93%
“…Under the light cycle of LD 12:12, the mRNA levels of BmCry2 , BmTim , and BmClk in Cry1-KD cells remained low, while the mRNA levels of BmPer and BmCyc recovered, and the amplitudes of clock genes increased ( Figure S4 ). More importantly, the expression of BmCry2 , BmPer , BmTim , and BmClk in Cry1-KD cells resumed oscillatory rhythm due to photoentrainment, which is consistent with the observations of several instances of clock gene knockout in silkworms [ 47 , 48 , 49 , 50 , 51 ]. We speculate that there are two possible reasons for this: (1) there is still a small amount of remaining BmCRY1 protein in Cry1-KD cells, which responds to photo signals and resets circadian rhythms; (2) other clock genes, such as BmCRY2, have the function of receiving photo signals.…”
Section: Discussionsupporting
confidence: 87%
“…Trunk has an ancient origin, which may predate Bilateria, while PTTH was initially shown to be arthropod-specific and according to a more recent investigation, it seems to be restricted to insects (Duncan et al, 2013;Jékely, 2013;De Oliveira et al, 2019). Timing of this stimulation is important, and studies in Diptera and Lepidoptera have observed that PTTH secretion has a circadian rhythmicity, but this remains to be fully elucidated (Niwa & Niwa, 2016;Bian et al, 2019;Kamiyama & Niwa, 2022;Qiu et al, 2023). Indeed neurons for light sensing might signal to neurons expressing PTTH that the appropriate photoperiod gate is open, and thereby regulate eclosion timing (Nijhout et al, 2014).…”
Section: ) Neuropeptides Regulate Ecdysteroid Biosynthesis Via Stimul...mentioning
confidence: 99%